The Role of the Ngayah Tradition in Moderating Work-Family Conflict and Job Stress on Teacher Performance in Ubud, Gianyar - Ni Putu Puspa Widyastiti; Ida Ayu Putu Widani Sugianingrat; I Putu Putra Astawa (Journal of Sustainable Development Science, 2026)
This study aims to analyze the influence of Work-Family Conflict and job stress on teacher performance in Ubud District, Gianyar Regency, and examine the moderating role of the ngayah tradition in this relationship. The study used a quantitative approach with a survey method, involving elementary and junior high school teachers as the population, with purposive sampling. The research instrument was a Likert-scale questionnaire, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct relationship and moderation. The results showed that Work-Family Conflict had no significant effect on teacher performance, while job stress had a significant positive effect, indicating that measurable work pressure can increase focus, creativity, and work responsibility (eustress). The ngayah tradition did not moderate the relationship between Work-Family Conflict and job stress on teacher performance, because its effectiveness depends on individual perceptions, workload, and social context. The conclusion of the study confirms that teacher performance is maintained thanks to social support, family understanding, and good role management. The integration of the ngayah tradition needs to be carried out adaptively to continue to provide benefits, support work-family balance, and strengthen performance according to the principles of Tri Hita Karana. Research suggestions include the implementation of effective time management, work-life balance training, coordination between teachers and schools, and regulating involvement in traditional activities so that cultural values become a source of motivation and not an additional burden.